2014
DOI: 10.12669/pjms.311.6317
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Knowledge, Attitude and Practices (Kap) Towards Diabetes and Diabetic Retinopathy in a Suburban Town of Karachi

Abstract: Objective:To assess the Knowledge, Attitude and Practices (KAP) towards diabetes and diabetic retinopathy in the general population of Bin Qasim Town (BQ), Karachi.Methods:An observational, cross-sectional study was approved by Research Ethical Committee of Al-Ibrahim Eye Hospital. It included every third household by stratified sampling in each Union Council of (BQ) Town, in the months of May to July 2013. The interview Questionnaire included 43 questions, of qualitative and quantitative aspects, which were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
55
4
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 8 publications
10
55
4
4
Order By: Relevance
“…The knowledge of diabetes as shown in Table 3 was significantly correlated with age in this study. This finding is similar to the findings in other studies [6] [8]. In Omani age, duration of diabetes (5 -10 years) and the region where the respondents reside positively influenced their knowledge [6].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The knowledge of diabetes as shown in Table 3 was significantly correlated with age in this study. This finding is similar to the findings in other studies [6] [8]. In Omani age, duration of diabetes (5 -10 years) and the region where the respondents reside positively influenced their knowledge [6].…”
Section: Discussionsupporting
confidence: 90%
“…The knowledge of the ocular complications of diabetes as shown in Table 5 was not significantly associated age, sex, occupation or duration of diabetes in our study similar to other studies [9]. In contrast, other studies found higher level of education, higher social class, age (>45 years) and Christianity as factors that influenced the knowledge of the respondents while others noted a higher female preponderance associated with knowledge [8] [10] [17]. The difference in methodology of these studies may account for these differences.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Also, it is associated with loss of productivity and quality of life, and may lead to additional socioeconomic burden. [5][6][7] About 4.8% (1.8 million) of global blindness was due to DR. [8][9][10] DR is a priority blinding disease and is now included in the disease control strategy of 'vision 2020' initiative. 11 Symptoms of diabetic retinopathy include; seeing spots or floaters, blurred vision, having a dark or empty spot in the center of vision and difficulty seeing well at night.…”
Section: Introductionmentioning
confidence: 99%
“…There are lots of studies that used the KAP analysis to assess the awareness of the community about different subjects. Memon et al 6 assessed the Knowledge, Attitude and Practices (KAP) towards diabetes and diabetic retinopathy in the general population of Karachi in 2015. Their results showed that there is a lack of knowledge of diabetes in the surveyed community, more marked in females, illiterate and the individuals not suffering from diabetes.…”
Section: Introductionmentioning
confidence: 99%